Campus outdoor environment, learning engagement, and the mental health of college students during the COVID-19 pandemic: From the perspective of students in different grades - Sun, Ning; Liu, Wanting; Zheng, Zhenhua (Frontiers in Public Health, 2023)
Introduction During COVID-19, the mental health of Chinese university students has been a pressing concern. But the internal mechanism of perceived campus outdoor environment and learning engagement affecting college students’ mental health during the COVID-19 pandemic has not been fully discussed. Methods The current study used cross-sectional data from 45 Chinese universities to explore the relationship among perceptions of campus outdoor environments, learning engagement, and college student mental health, and focused on differences among college students in different grades. Results Our study revealed the mental health problems of Chinese college students during the COVID-19 pandemic were more severe. The mental health of postgraduates was generally poor, and their risk of depression was higher than that of undergraduates. More importantly, for postgraduates, the direct impact of the perceived campus outdoor environment on their mental health was stronger. For undergraduates, the indirect impact of learning engagement on the effect of the perceived campus outdoor environment on their mental health was stronger. Conclusion The results of the study have implications for campus planners, landscape architects, and university planners to pay particular attention to the needs of postgraduates for campus outdoor environments, which is of great significance to improve the overall mental health of students during the COVID-19 pandemic.